2023
DOI: 10.1038/s41598-023-35459-z
|View full text |Cite
|
Sign up to set email alerts
|

Episodic transient deformation revealed by the analysis of multiple GNSS networks in the Noto Peninsula, central Japan

Abstract: Since November 30, 2020, an intense seismic swarm and transient deformation have been continuously observed in the Noto Peninsula, central Japan, which is a non-volcanic/geothermal area far from major plate boundaries. We modeled transient deformation based on a combined analysis of multiple Global Navigation Satellite System (GNSS) observation networks, including one operated by a private sector company (SoftBank Corp.), relocated earthquake hypocenters, and tectonic settings. Our analysis showed a total disp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…Earthquake migration itself can be explained by effects other than pore pressure and fluid migration, such as aseismic slips and earthquake interactions (Helmstetter & Sornette, 2002;Im & Avouac, 2023). Geodetic data analysis suggests that aseismic deformation occurred during this swarm (Nishimura et al, 2023), and the aseismic slip occurrence during fluid migration is consistent with predictions from numerical simulations of the response of a fault under fluid intrusion (Bhattacharya & Viesca, 2019;Eyre et al, 2019;Wynants-Morel et al, 2020;Yoshida et al, 2021). Recent observations support the occurrence of aseismic slip during fluid intrusion for both natural and fluid-injection-induced seismicity (Cornet et al, 1997;Danré et al, 2022;De Barros et al, 2020;Guglielmi et al, 2015;Hatch et al, 2020;Wei et al, 2015;Yoshida & Hasegawa, 2018b;Yukutake et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Earthquake migration itself can be explained by effects other than pore pressure and fluid migration, such as aseismic slips and earthquake interactions (Helmstetter & Sornette, 2002;Im & Avouac, 2023). Geodetic data analysis suggests that aseismic deformation occurred during this swarm (Nishimura et al, 2023), and the aseismic slip occurrence during fluid migration is consistent with predictions from numerical simulations of the response of a fault under fluid intrusion (Bhattacharya & Viesca, 2019;Eyre et al, 2019;Wynants-Morel et al, 2020;Yoshida et al, 2021). Recent observations support the occurrence of aseismic slip during fluid intrusion for both natural and fluid-injection-induced seismicity (Cornet et al, 1997;Danré et al, 2022;De Barros et al, 2020;Guglielmi et al, 2015;Hatch et al, 2020;Wei et al, 2015;Yoshida & Hasegawa, 2018b;Yukutake et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
“…fault network (Yoshida, Uno, et al, 2023). Previous studies have suggested that fluid movement at depth and the accompanying aseismic deformation are involved in this swarm (Amezawa et al, 2023;Nakajima, 2022;Nishimura et al, 2023;Yoshida, Uno, et al, 2023). The presence of a deeper low-seismic-velocity region and a distinct seismic reflector led to the inference that the upward migration of slab-derived fluids triggered this swarm (Yoshida, Uno, et al, 2023).…”
mentioning
confidence: 87%
“…Several studies of intraplate earthquakes along the eastern margin of the Japan Sea have proposed a link between crustal fluids and the complex structures of the source regions in the reactivation of these ancient faults (Kato et al, 2009(Kato et al, , 2011Matsumoto et al, 2005;Uyeshima et al, 2005;Yoshimura et al, 2008). Nishimura et al (2023) used geodetic data to suggest that the upwelling fluid spread at ∼16 km depth through an existing shallow-dipping permeable fault zone and then diffused into the fault zone (Figure 4). Amezawa et al (2023) implied that crustal fluid is a major factor influencing the spatiotemporal evolution of the long-lasting Noto Peninsula seismic swarm based on diffusive hypocenter migrations.…”
Section: Discussionmentioning
confidence: 99%
“…Regional GNSS (Global Navigation Satellite System) positioning suggests a volumetric increase of ∼1.4 × 10 7 m 3 in the first 3 months of the swarm, suggesting that fluid migration may be the cause of the Noto earthquake swarms ( 2 ). Amezawa et al ( 3 ) assert that crustal earthquake swarms exhibit distinct spatiotemporal patterns of earthquake migration, characterized by clusters that originate at depth and migrate upward, suggesting the presence of fluids as the driving factor behind such swarms; in the case of Noto, the source of such crustal fluids is likely from a concealed magma system ( 4 ) or slab-derived fluids ( 5 ).…”
Section: Introductionmentioning
confidence: 99%